Inert and Adsorptive Tracer Tests for Field Measurement of Flow‐Wetted Surface Area. Issue 8 (16th August 2018) - Hawkins, Adam J.; Becker, Matthew W.; Tester, Jefferson W.
Abstract: Field tests in a discrete rock fracture validated a combined inert/adsorbing tracer test method to estimate the contact area between fluids circulating through a fracture and the bulk rock matrix (i.e., flow‐wetted surface area, A). Tracer tests and heat injections occurred at a mesoscale well field in Altona, NY. A subhorizontal bedding plane fracture ∼7.6 m below ground surface connects two wells separated by 14.1 m. Recovery of the adsorbing tracer cesium was roughly 72% less than the inert tracer iodide. Using an advection‐dispersion‐reaction model in one‐dimension, the adsorbing/inert tracer method identified substantial flow channelization. These results are consistent with Ground Penetrating Radar (GPR) and thermal sensors. All characterization methods suggest circulating fluids were concentrated in a narrow, 1–2 m wide channel directly connecting the injection and production well. The inert/adsorbing tracer method identified two flow channels with areas of 28 and 80 m 2 . A one‐dimensional heat transport model predicted production well temperature rises 20.5°C in 6 days, whereas measured temperature rise was 17.6°C. For comparison, two‐dimensional heat transport through a fracture of uniform aperture (i.e., homogeneous permeability) predicted roughly 670 days until production well temperature would rise 17.6°C. This suggests that the use of a fracture of uniform aperture to predict heat transport may drastically overpredict the thermal performance of a geothermal system. In the context of commercial geothermal reservoirs, the results of this study suggest that combined inert/adsorbing tracer tests could predict production well thermal drawdown, leading to improved reservoir monitoring and management. Key Points: Combined inert/adsorptive tracer testing accurately predicts heat transport Conventional hydraulic and tracer tests fail to accurately estimate fracture aperture Channeled flow caused rapid heat transport between an injector/producer well pair